2020
DOI: 10.1371/journal.pone.0234425
|View full text |Cite
|
Sign up to set email alerts
|

Confronting challenges to opioid risk mitigation in the U.S. health system: Recommendations from a panel of national experts

Abstract: BackgroundAmid the ongoing U.S. opioid crisis, achieving safe and effective chronic pain management while reducing opioid-related morbidity and mortality is likely to require multi-level efforts across health systems, including the Military Health System (MHS), Department of Veterans Affairs (VA), and civilian sectors. ObjectiveWe conducted a series of qualitative panel discussions with national experts to identify core challenges and elicit recommendations toward improving the safety of opioid prescribing in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Similar to other studies, 8,12,31 many of the limitations reported by STORM program patients related to a need for additional resources to treat pain or tapering adverse effects. Nearly half of patients expressed frustration with nonpharmacological pain management suggestions provided by pharmacists; patients found these suggestions redundant to options they had already tried or unaffordable.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Similar to other studies, 8,12,31 many of the limitations reported by STORM program patients related to a need for additional resources to treat pain or tapering adverse effects. Nearly half of patients expressed frustration with nonpharmacological pain management suggestions provided by pharmacists; patients found these suggestions redundant to options they had already tried or unaffordable.…”
Section: Discussionsupporting
confidence: 62%
“…6,7 These guidelines necessitate providers initiating conversations about opioid tapering with patients and developing action plans. 8 However, these conversations can be challenging and time consuming for primary care providers (PCPs), and most PCPs lack sufficient training in managing the tapering process. PCPs have reported stress and burnout related to caring for patients requiring opioid tapers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacist had the opportunity to review how patients were managing their analgesics and was able to provide recommendations to them on pharmacological and non-pharmacological strategies to improve overall pain management. Furthermore, the pharmacist was able to assess the patient’s understanding of the opioid management plan and provide education on the anticipated duration of opioid use, to minimize the risk of these medications inadvertently being prescribed for a prolonged period [ 19 ]. Numerous studies have demonstrated the benefits that patient education can have on reducing opioid use and improving pain and functional outcomes [ 6 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because multiple prescribers or multiple pharmacies may increase risk of drug duplication, a collaborative team approach headed by a single prescriber with ready access to pharmacist medication review and consultation is likely the best option to protect older adults with dementia from potential harms of drug duplication. 34 , 35 …”
Section: Discussionmentioning
confidence: 99%